(untitled) (Bangladesh Journal of Medicine, 2021)
Background: Renal transplantation remains the treatment of choice for end-stage renal disease, as the procedure not only improves quality of life, but also markedly increases patients’ survival rates. Organ and patient survival rates are important issues of interest post-transplantation.The aims of this study were to analyze the data for immediate post-procedure outcome and one-year graft survival after live related kidney transplantation. Methods:A retrospective study was conducted in Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) General Hospital, Dhaka, Bangladesh between November 2004 and September 2019. Data for a total of 132 live related kidney transplant recipients were collected in pre-formed questionnaire from the hospital records. Results:Total patients were 132 including 97 (73.5%) males. Mean age of recipients was 36.8±10.4 years. Mean post-transplantation hospital stay was 13.6±3.4 (range 9 to 30) days. During postoperative hospital stay, 6 (4.6%) patients required haemodialysis due to delayed graft function and high levels of serum creatinine. During discharge, 117 (88.6%) recipients had normal renal function (mean serum creatinine level 1.15±0.21 mg/dl) and 15 (11.4%) patients showed improvement in serum creatinine levels but did not reach normal value (mean serum creatinine levels 3.25±2.35 mg/ dl). All patients were regularly followed-up in post-transplant clinic (3 patients did not complete 1 year) after transplantation. After the first year of kidney transplantation, patient and graft survival rates were 90.7% (117/129) and 82.9% (107/129) respectively. Conclusions: Eighty-eightpercent live related kidney transplant recipients had normal renal function immediate post-surgery and one-year graft survival rate was over eighty percent in this study. Bangladesh J Medicine January 2021; 32(1) : 39-42